The Importance of Ethics Education in a Digital Society to Face Netiquette Challenges That Arise Among Students at SMAN 10 Mataram - Andriawan Andriawan; Yuniati Lestari; Rifki Rahman; Isbul Jannah; Putri Hias Permata; Yayan Aris Cahyadi; Edy Herianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to analyze the importance of digital ethics education in facing netiquette challenges among students at SMAN 10 Mataram. The research method used is descriptive qualitative with a case study approach. Data was collected through literature study, observation, interviews and documentation with students and teachers at the school. The research results show that most students do not fully understand the rules and norms that apply when interacting in the digital world. Digital ethics education can increase students' awareness of the importance of maintaining privacy, respecting other people's opinions, and avoiding negative actions such as cyberbullying, spreading hoaxes, using harsh and impolite language.